Analisis kadar PM10 dan CO serta keluhan pernapasan pada petugas operasional terminal peti kemas PT PELINDO Belawan tahun 2023 - Ramadhani, Adinda Nur; Santi, Devi Nuraini (TROPHICO: Tropical Public Health J., 2023)
Air pollution and respiratory symptoms among operational staff at container terminal of PT. PELINDO Belawan might be caused by emission of PMâ‚â‚€ and CO from operational container trucks. This research aims to assess PMâ‚â‚€ and CO levels, also to investigate respiratory symptoms among operational staff at container terminal of PT. PELINDO Belawan. This is an observational research with cross-sectional design study. From a population of 699 individuals, 88 samples were obtained using purposive sampling technique. Air quality data was collected through direct measurements at three different locations, while respiratory symptoms data was gathered through staff interviews. PMâ‚â‚€ level at the container terminal had exceeded the standard limit, with the highest concentration recorded at the entrance gate, reaching 193 Âµg/NmÂ³. Whereas, CO level remained within the acceptable range. Trucks flow observation over a week revealed that the highest flow occurred on Tuesday, with 3,037 trucks, while the lowest flow was on Sunday, with a total of 223 trucks. Among the 88 respondents, 40 individuals (45.5%) experienced respiratory symptoms, with the most common complaint, reported by 25 individuals (65%), being runny or congested nose. Most respiratory symptoms occurred at unpredictable times, as reported by 35 individuals (39.8%). Container terminal of PT. PELINDO Belawan is recommended to enforce mask usage while working and respiratory health check-ups regularly for the operational staff to monitor respiratory health of the operational staff, as well as planting trees to mitigate pollutant levels in the air.